2020
DOI: 10.1093/jas/skaa278.226
|View full text |Cite
|
Sign up to set email alerts
|

375 Economic Consequences of Pregnancy Loss in Beef Cattle

Abstract: Over the last four decades, several advances in reproductive biotechnologies have helped beef producers improve genetic traits of their cattle, tighten the breeding season and shorten the calving season, leading to an increase in overall profitability of cow-calf production systems. However, even with these advancements, reproductive failure and embryo mortality are still a major cause for economic loss in beef production. Recently, we projected a loss of $6.25 per exposed cow for every 1% decrease in pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Cow-calf production is the foundation of the U.S. beef industry, representing 86% of beef operations and 84% of the beef cattle population in the country [7]. However, reproductive inefficiency has been a significant cause of economic loss and a limiting factor for the sustainability of the beef industry [8][9][10]. The annual gross loss (due to pregnancy failure) of beef females is estimated to cost USD 2.8 billion in the United States [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cow-calf production is the foundation of the U.S. beef industry, representing 86% of beef operations and 84% of the beef cattle population in the country [7]. However, reproductive inefficiency has been a significant cause of economic loss and a limiting factor for the sustainability of the beef industry [8][9][10]. The annual gross loss (due to pregnancy failure) of beef females is estimated to cost USD 2.8 billion in the United States [10].…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability of a cow-calf production system relies on the efficiency of reproductive performance per cow. However, a decline in cattle fertility has led to increased reproductive failure [ 1 , 2 ], which is a challenge for beef producers and a significant cause of economic loss [ 3 ]. Fertility is a lowly heritable, multifactorial trait affected by genetic, environmental, and management factors [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fertility is a lowly heritable, multifactorial trait affected by genetic, environmental, and management factors [ 2 , 4 , 5 ]. Despite the limited selection response to traditional selective breeding strategies, reproductive and genomic technologies have provided opportunities to improve reproductive efficiency [ 3 , 6 ]. Several candidate genes and biological processes have been identified through genome-wide association studies (GWAS) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in 2008, it was shown that in Florida, $75 was lost per failed pregnancy during the breeding season [27], and that loss might even be higher if adjusted for inflation. Despite the increase in technology, reproductive failure and loss of embryo issues are still around, and an estimated loss of $2.8 billion in the US beef industry per year might happen if nothing is done [28]. Given the identified failures and what could be gained if a heifer gets pregnant early in the breeding season, it is essential to study the fertility traits further to increase the number of calves born alive and reduce the cost related to reproductive failure.…”
Section: Importance Of Fertility Traitsmentioning
confidence: 99%
“…Despite the previously reported data scarcity and low heritability status of reproductive traits that hinder the genetic progress in beef cattle [44][45][46], these traits are believed to have a pivotal role in the development of the beef industry. Mercadante et al predicted a loss of $21 billion of revenue due to the failure to produce a live calf at weaning and the cost of breeding [28]. Morrey and Biased predicted that the beef industry would lose over $210 million due to late breeding heifers [47] as it is phenotypically related to cows continued reproductive success (i.e., stayability).…”
Section: Introductionmentioning
confidence: 99%